The limits of the imaginary: Challenges to intervening in future speculations of memory, data, and algorithms. (February 2021) - Markham, Annette
Over 3 years, researchers, artists, and activists collaborated on eight public engagement experiments in five countries. All focused on building critical consciousness about digital futures. The interventions worked: Once participants broke through the seamlessness of interface surfaces, they immediately thought more critically about how digital platforms actually operate. Yet even as participants reached into these black boxes, they did not imagine alternatives. This article offers a critical theory reading of the theme of inevitability, using the concept of discursive closure, whereby we can see how particular values and (infra)structures are naturalized, neutralized, and legitimated, closing off discussion of alternatives that might counter current hegemonic power. This article highlights the importance of considering iterative formats for speculative interventions, whereby facilitators can focus not only on imagining new or different digital futures, but find creative ways to identify and help overcome the current resignation to the inevitable.